Review: Curry leaves and their role in naturally preserving meat proteins and meat products - Mohammed, Lina Sameer; Hashem, Alia Ziearah; Salman, Mohammed Alwan (Journal of agricultural, environmental and veterinary sciences, 2025)
This study aimed to identify the nutritional and medicinal importance of the curry plant (Murraya koenigii). This is due to its richness in some bioactive substances, such as phenols, flavonoids, volatile oils, vitamins, minerals, and pigments. Curry is a bioactive plant, characterized by its antioxidant and antibacterial properties, which has made it widely used in many food, medical, and therapeutic applications. Many studies have aimed to identify its components and study the variation among them from a nutritional and therapeutic perspective, in addition to incorporating them into food products, especially red meat and poultry. This review reviews the most prominent of these studies and seeks to highlight the role of curry leaves as a natural preservative.
Keywords: Curry leaves components; nutritional and therapeutic usefulness; antioxidant activity; bacterial inhibition